Characteristics treatment outcomes and experiences of COVID 19 patients under Home Based Care in Kapyelebyong district in Uganda - Eudu, James; Benon, Wanume; Milton, W. Musaba; Ritah, Nantale; Vivian, Mutaki; Brendah, Nambozo; David, Okia; David, Soita; Agnes, Napyo; Joseph, K. B. Matovu; Racheal, Namulondo; Jovani, Lubaale; et al. (Tropical Medicine & International Health, 2022)
Abstract Background: A rapid increase in community transmission of COVID-19 across the country overwhelmed Uganda’s health care system. In response, the Ministry of Health adopted the home-based care strategy for COVID-19 patients with mild-to-moderate disease. We determined the characteristics, treatment outcomes and experiences of COVID-19 patients under home-based care during the second wave in Kapelebyong district, in eastern Uganda. Methods: We conducted a sequential explanatory mixed-methods study. We frst collected quantitative data using an interviewer-administered questionnaire to determine characteristics and treatment outcomes of COVID-19 patients under home-based care. Cured at home was coded as 1 (considered a good outcome) while being admitted to a health facility and/or dying were coded as 0 (considered poor outcomes). Thereafter, we conducted 11 in-depth interviews to explore the experiences of COVID-19 patients under home-based care. Multivariable logistic regression was used to assess factors associated with poor treatment outcomes using Stata v.15.0. Thematic content analysis was used to explore lived experiences of COVID-19 patients under home-based care using NVivo 12.0.0 Results: A total of 303 study participants were included. The mean age±standard deviation of participants was 32.2 years±19.9. Majority of the participants [96.0% (289/303)] cured at home, 3.3% (10/303) were admitted to a health facility and 0.7% (2/303) died. Patients above 60 years of age had 17.4 times the odds of having poor treatment outcomes compared to those below 60 years of age (adjusted odds ratio (AOR): 17.4; 95% CI: 2.2–137.6). Patients who spent more than one month under home-based care had 15.3 times the odds of having poor treatment outcomes compared to those that spent less than one month (AOR: 15.3; 95% CI: 1.6–145.7). From the qualitative interviews, participants identifed stigma, fear, anxiety, rejection, not being followed up by health workers and economic loss as negative experiences encountered during home-based care. Positive lived experiences included closeness to friends and family, more freedom, and easy access to food. Conclusion: Home-based care of COVID-19 was operational in eastern Uganda. Older age (>60 years) and pro‑ longed illness (>1 months) were associated with poor treatment outcomes. Social support was an impetus for homebased care
Keywords: Home-based care, COVID-19, Uganda, Treatment outcome, Stigma, SARS-COV-2